WANPRESTASI DALAM HUKUM PERJANJIAN DAN UTANG DALAM HUKUM KEPAILITAN - Ribi, Hikmawati; Zakiah, Zakiah (Restorative Journal, 2024)
ABSTRACT The phenomenon of resolving defaults on the basis of perceived debt using bankruptcy law mechanisms has become widespread. It is not uncommon for the bankrupt respondent to deliberately default in order to retaliate against the opposing party who has defaulted previously. This journal's research points to the concept of default in contract law that can be fully applied to the concept of debt in bankruptcy law.Research using normative legal research methods through statutory approaches, case approaches, comparative approaches and conceptual approaches. Analysis of legal materials is carried out using an exploratory qualitative approach using interpretive, systematic, evaluative, constructive and argumentative techniques.The research results show that not all defaults can be categorized as debts in bankruptcy, except if the achievements in question are achievements in the field of business activities/trade debts. Defaults are only responsible for creditors who have made an agreement, but in bankruptcy law, they must be looked at and the resolution will involve all other creditors as well. Keywords: Law, Default, Bankruptcy.